How can scientific assessment drive climate action? An interactive discussion: UK Pavilion COP28 - Department for Energy Security and Net Zero, United Kingdom (Department for Energy Security and Net Zero. 2024, 2024)
This is a video recording of a session at the UK Pavillion at COP28 where the CGIAR Climate Impact Platform Lead (Aditi Mukherji) spoke along with the Chair of the IPCC AR7 on the role of agri-food systems and systems transition in the next AR7 cycle.